Analisis Bentuk Kewirausahaan Mahasiswa pada Revolusi Industri 4.0 di Perguruan Tinggi Kota Pekanbaru - Alfiah Alfiah; Meimunah S. Moenanda; Darni Darni; Ismail Ismail (Eklektik : Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
The 4.0 industrial revolution made students more creative in many entrepreneurship forms. This study aims to determine how students are interested in entrepreneurship and find out the forms of entrepreneurship that are of interest to students at tertiary institutions in Riau province. 150 students from 3 tertiary institutions in Pekanbaru, namely Sultan Syarif Kasim Riau State Islamic University (UIN Suska Riau), Riau University (UR) and Riau Islamic University (UIR) became participants in this study. The research instrument in the form of a questionnaire was filled out by students and then analyzed to see the percentage of student interest and the forms of entrepreneurship they had. The results showed that students in 3 colleges in the city of Pekanbaru have an interest in entrepreneurship by utilizing the 4.0 industrial revolution. They utilize information technology in terms of ease of internet access with the platform of social media accounts they have in entrepreneurship. Then, the form of student entrepreneurial activities is engaged in online trading business, Fintech (Finance Technology), Cloud hosting and On-Demand service (Services).